Pelatihan Pembuatan Sabun Cuci Piring Sebagai Upaya Peningkatan Efektivitas Dan Peluang Usaha Bagi Ibu Rumah Tangga Di Desa Pandau Jaya - Elida Gultom; Nova Syafrina; Lamin Lamin; Jeli Nata Liyas (BADAN PENERBIT STIEPARI PRESS, 2024)
This community service was carried out in Pandau Jaya Village, Siak Hulu District, Kampar Regency, Riau Province. This activity was held on Sunday 24 September 2023 with the theme Training on Making Dish Soap as an Effort to Increase Effectiveness and Business Opportunities for Housewives. Dish washing soap is a product that is really needed in the household to keep kitchen equipment clean. The need for dishwashing soap causes people to have to allocate a large amount of money every month to shop for dishwashing soap. The aim of carrying out this service activity is to provide training and direction on making dishwashing soap in order to reduce community expenditure on purchasing dishwashing soap as well as to create business opportunities for housewives. The method of implementing this service is carried out in two ways, namely the lecture method and practice. It is hoped that the results of this community service activity will increase the understanding and ability of Pandau Jaya village housewives to make dishwashing soap so that it is useful and has an impact on the family economy.